Macroeconomic effects of output volatility in Ukraine - Shevchuk, Viktor (Efekty makroekonomiczne zmienności produkcji w gospodarce Ukrainy, 2019)
This paper focuses on several macroeconomic effects of the output volatility in Ukraine. Our findings suggest that the volatility that originates from the gross domestic product (GDP) has a sizeable, negative and statistically significant effect on economic growth and investments while being complementary to industrial production (no impact on consumption and consumer prices has been detected). The results also indicate asymmetric exchange rate effects upon GDP and industrial production growth. Among other results, it has been found that (i) output volatility has expansionary effects on three out of five sectors (manufacturing, food processing and power generation), with a likely contractionary effect on the steel-making industry, (ii) exchange rate depreciation stimulates investments, but at the expense of higher inflation and lower consumption, (iii) output volatility is associated with lower money supply and a decrease in the interest rate, with a negative impact on the budget balance
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 113-124